Arduino Training for High School Students: Improving Technology Literacy and Creativity in the Digital Age - Gunawan, Bodi; Hamdani, Dedy; Setiawan, Iwan; Lora, Haditya A (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2025)
Background of study: This community service activity aimed to address the gap in technological literacy and practical skills among students at SMAN 6 Bengkulu Tengah, Indonesia, by introducing the Arduino microcontroller platform as a tool for enhancing STEM education.Aims and scope of paper: The primary objective was to assess the effectiveness of project-based Arduino training in improving students' understanding of electronics and programming. The study specifically evaluated cognitive gains, development of practical skills, and increased student confidence.Methods: The program employed a participatory approach, combining interactive lectures, hands-on project development, and pretest and posttest evaluations using the Kahoot! platform. The training involved 41 participants and included collaborative project work in groups.Result: The intervention resulted in a significant 36% increase in posttest scores (from 42% to 78%), with notable improvements in component knowledge (+82%) and schematic understanding (+79%). Additionally, 87% of participants reported increased confidence in experimenting with electronics projects.Conclusion: Findings demonstrate that Arduino-based training effectively enhances technological literacy and STEM skills among high school students. The study recommends integrating microcontroller platforms into physics curricula and fostering school-university partnerships for sustainable implementation through teacher training, equipment provision, and module development aligned with the Merdeka Curriculum.